Analysis of the literature on 3D printing in healthcare with reference to pharmaceuticals using a bibliometric approach - Virendra S. Ligade, Akash Chimegave (Journal of Applied Pharmaceutical Science, 2022)
3D printing is an emerging digital technology. Approximately 30 years since its introduction, 3DP technology is set to revolutionize research and teaching laboratories. The said technology has revolutionized the development of modified dosage formulations and regenerative medicine. The aim of the present study is to analyze the trends in research publications in 3DP in pharmaceuticals using the bibliometric method. A literature search was carried out to extract all publications related to 3DP in pharmaceuticals using the PubMed database. The data were extracted for the years 2010–2020. Insights were categorized based on year of publications, document types, authors, publication source titles, country, citations, research areas, and keyword analysis. An upward trend in the growth of publications is witnessed for the years 2020 and 2019 with 23.21% and 22.81% of records, respectively. Our retrieved publications indicated that the United States was the leading country in the literature with 203 publications (20.13%). In 3DP research publication trends, researchers from USA received the highest number of citations. Words such as “printing,” “3D printing,” “drug,” “hydrogels,” “tablets,” “tissue,” “bioprinting,” “drug delivery,” and “pharmaceutical” were found as high-frequency keywords. Alvaro Goyanes was found to be most productive author with n = 42 (4.16%) publications. Currently, 3DP is in a primitive stage in the field of pharmaceuticals. There has been an upsurge in interests in 3DP in pharmaceuticals. It is evident by an increasing number of research publications in recent years. Researchers and various authors had expressed the positive aspect of 3DP. The research publication trends may continue and increase with robust studies in the field of 3DP in pharmaceuticals.
Keywords: 3D printing, pharma, pharmaceuticals, technology, bibliometric research